2017
DOI: 10.1021/jacs.7b02839
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Prolyl-4-hydroxylase Structure Steers a Ferryl Oxidant toward Scission of a Strong C–H Bond

Abstract: Prolyl-4-hydroxylase (P4H) is a non-heme iron hydroxylase that regio- and stereospecifically hydroxylates proline residues in a peptide chain into R-4-hydroxyproline, which is essential for collagen cross-linking purposes in the human body. Surprisingly, in P4H, a strong aliphatic C-H bond is activated, while thermodynamically much weaker aliphatic C-H groups, that is, at the C and C positions, are untouched. Little is known on the origins of the high regio- and stereoselectivity of P4H and many non-heme and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 107 publications
11
81
0
1
Order By: Relevance
“…46,47 Thereafter, dioxygen was placed in a position near the active site Asn residues. A standard procedure was followed for the subsequent set-up of the system, as described in more detail elsewhere, [38][39][40][48][49][50][51] and briefly summarized here. The enzyme model was set up using procedures proposed by Thiel et al 52,53 The substrate bound enzyme structure with dioxygen bound was protonated to pH 7 with the PROPKA method using the PDB2PQR web service, 54 whereby all Glu and Asp side chains were deprotonated and all Arg and Lys side chains protonated.…”
Section: Methodsmentioning
confidence: 99%
“…46,47 Thereafter, dioxygen was placed in a position near the active site Asn residues. A standard procedure was followed for the subsequent set-up of the system, as described in more detail elsewhere, [38][39][40][48][49][50][51] and briefly summarized here. The enzyme model was set up using procedures proposed by Thiel et al 52,53 The substrate bound enzyme structure with dioxygen bound was protonated to pH 7 with the PROPKA method using the PDB2PQR web service, 54 whereby all Glu and Asp side chains were deprotonated and all Arg and Lys side chains protonated.…”
Section: Methodsmentioning
confidence: 99%
“…With all methods, apart from BP86, the triplet 1 IV -O is the ground state in agreement with Mçssbauer data reported above.D espite these fluctuations in spin-state energies,p revious studies of ours;h owever,s howed that changing the density functional method generally does not change regio-and stereo-selectivities of ac hemical reaction but only affects the relative energies. [38,39] In the triplet and quintet spin states, 1 II -H 2 O 2 -a and 1 II -H 2 O 2 -b are close in energy with as mall preference of the latter at B3LYP level of theory.W ell higher in energy than these quintet spin H 2 O 2 complexes are the triplet spin states., Therefore,the triplet spin 3 1 II -H 2 O 2 will not play arole in the reaction mechanism leading to the formation of the Fe IV -oxo.…”
mentioning
confidence: 87%
“…For example, prolyl‐4‐hydroxylase is an α‐ketoglutarate dependent nonheme iron dioxygenase that catalyzes the biosynthesis of (2 S ,4 R )‐4‐hydroxyproline from proline; an important component of collagen in the skin . Computational modeling showed that thermodynamically C 5 ‐hydroxylation of proline should be the energetically favorable pathway, yet this product is not formed by this enzyme . Similarly, the nonheme iron dioxygenase AsqJ performs two steps in the biosynthesis process of 4′‐methoxy‐viridicatin; one involving a desaturation and the other an epoxidation reaction .…”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%
“…Thermodynamically, however, the weakest C−H bond of proline is at the C 5 position and hence, the question is how the protein can block a low energy hydrogen atom abstraction pathway from the C 5 ‐H position and drive the reaction to the thermodynamically unfavorable C 4 ‐hydroxylation pathway instead. To understand how P4H avoids hydrogen atom abstraction from the C 5 ‐H position in favor of C 4 ‐H hydroxylation, a series of detailed computational studies were performed …”
Section: Second‐coordination Sphere Effects In Nonheme Iron Enzymesmentioning
confidence: 99%